On the Monthly Distribution of Precipitation in Sarawak - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir; Ambak, Mohd Azmi; Rang, Lim You (Universiti Putra Malaysia Press, 2000)
In this investigation the study of the monthly distribution of precipitation and the rainfall variability of Sarawak is addressed. The principal results of this manuscript may be summarized as follows; (i) the total amount rainfall of each station remains unchanged during the months of the southwest monsoon season, (ii) no definite inverse correlation between rainfall variability and precipitation has been established, and (iii) lesser values of rainfall variability are reported south of Sibu during the first six months of the year.